Human trafficking : interdisciplinary perspectives - Burke, Mary C. (New York [etc.] Routledge, 2013)
The practice of one human being exploiting another in slavery-like conditions is not new. Today, it is called human trafficking. Social, political, and economic forces over the past 60 years have changed how and why this human rights abuse occurs.
Keywords: Derecho internacional humanitario; Tráfico de personas; Libros electrónicos